Upaya Hukum bagi Pekerja Perusahaan tidak Melaksanakan Employee Branding - Hendartama, Alfi; Ambarwati, Mega Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Employee branding is one of the marketing for companies that focuses on employees performing to improve creativity, motivation, skills and performance towards the company. In the company has its own branding to introduce the company to the public in Indonesia, so that the company is better known in terms of company performance. Workers in the company always have the motivation to improve performance in order to improve performance, creativity and make the company better known. The obligations of workers in the company have many aspects that are carried out, one example is employee branding, to maintain the company's image from the public's view and competitors from other companies